The misery of international law : confrontations with injustice in the global economy - Linarelli, John; Salomon, Margot E.; Sornarajah, M. (Oxford : Oxford University Press, 2018)
International economic law is not neutral in the interests it protects and offends. This text examines how current international legal regimes constitute and sustain economic injustice, and presents a forceful case for ridding international law of its hallmarks of fostering poverty, inequality, and dispossession.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 18, 2018).
Keywords: International law -- Economic aspects; Poverty; Equality; International economic relations; Globalization; Law; International law